2002
DOI: 10.1002/1521-4141(200208)32:8<2199::aid-immu2199>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

CD8 lethargy in the absence of CD4 help

Abstract: CD4 T cell help was proposed to have a pivotal role in orienting CD8 T cell responses to antigen stimulation. By activating antigen‐presenting cells (APC), CD4 cells would induce their expression of costimulatory molecules, the "signal two" required to induce full CD8 activation, preventing CD8 tolerance. Recent data on this subject is contradictory, as the absence of help did not alwaysresult in CD8 tolerance. These differences were attributed either to the presence of residual CD4 help or, respectively to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
91
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(98 citation statements)
references
References 47 publications
7
91
0
Order By: Relevance
“…8,9 It was demonstrated both in viral infection and tumor models that CD4 þ T cells support CD8 þ T cells for full activation by providing costimulatory signals and necessary cytokines. [32][33][34][35] Nonetheless, a concern on the use of PBLs may arise because a portion of CD4 þ T cells exerts Th2 response. However, a number of studies demonstrated that the antigen-specific support from both Th1 and Th2 cells is also critical when CD8 þ T cells are rechallenged for memory responses.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 It was demonstrated both in viral infection and tumor models that CD4 þ T cells support CD8 þ T cells for full activation by providing costimulatory signals and necessary cytokines. [32][33][34][35] Nonetheless, a concern on the use of PBLs may arise because a portion of CD4 þ T cells exerts Th2 response. However, a number of studies demonstrated that the antigen-specific support from both Th1 and Th2 cells is also critical when CD8 þ T cells are rechallenged for memory responses.…”
Section: Discussionmentioning
confidence: 99%
“…Maintenance of memory CD4 and CD8 cells seems to be independent of antigen or MHC class II and I molecules, respectively [20,21]. The generation of efficient CD8 memory T cells requires the presence of CD4 T cells [22][23][24][25]. Longevity of memory T cells appears to be cytokine driven.…”
Section: Introductionmentioning
confidence: 99%
“…While CD8 ϩ T cells are known to be an important immune effector mechanism for the elimination of HIV-infected cells, it is increasingly apparent that CD4 ϩ T cells provide essential help to other components of the adaptive immune response and are also crucial for the induction of effective HIV immunity (5-7). In particular, CD4 ϩ T cells appear to play an important role in maintaining functional CD8 ϩ T-cell responses (8)(9)(10)(11)(12)(13)(14)(15).…”
mentioning
confidence: 99%